Comparative government and politics an introduction - McCormick, John; Hague, Rod; Harrop, Martin (Bloomsbury Academic, 2022)
Offering a comprehensive introduction to the comparison of governments and political systems, this new edition helps students to understand not just the institutions and political cultures of their own countries but also those of a wide range of democracies and authoritarian regimes from around the world. This new edition offers A revised structure to aid navigation and understanding, New learning features, 'Using Theory' and 'Exploring Problems', designed to help students think comparatively, Empirical global examples, with increased coverage of non-Western scholarship and analyses, Coverage of important contemporary topics including: minorities; LGBTQ+ issues; identity politics; women in politics; political trust; populism; Covid-19. Featuring a wide range of engaging learning features, this book is an essential text for undergraduate and postgraduate courses on Comparative Politics, Comparative Government, Introduction to Politics and Introduction to Political Science.